Role of colloids in the transfer and dispersion of trace elements into river waters through a former mining district - Heydon, Marie; Perez Serrano, Lucia; Schreck, Eva; Causserand, Carole; Pokrovsky, Oleg S.; Behra, Philippe; Viers, Jérôme (Applied geochemistry)
Characterizing the different chemical forms of trace elements in surface inland waters of mining regions is very important to understand the mechanisms underlying metal(loid) transport, their accumulation and toxicity, especially when waste storage areas are closely linked to the hydrographic network. This study focuses on the oldmining district of Salsigne in the Orbiel Valley (France), which was at one time the largest gold mine in Europe and the world's largest arsenic mine. Our objective was to better understand the factors governing the transport of As and to investigate the role of colloidal matter as vector of major (Al, Ca, Fe, Mg) and trace (As, Pb, REE) elements in waters. A field sampling campaign was carried out during high water season to collect samples from the Orbiel River and its tributaries. In situ (ultra)filtrations at different cut-off thresholds (0.22 μm, 0.025 μm, 100 kDa and 3 kDa) were performed and physicochemical parameters (conductivity, pH, alkalinity, Dissolved Organic Carbon: DOC, anions, major cations, and metal(loid)s concentrations) of river water were assessed in all fractions. Results showed decreasing concentrations of DOC, Fe, Al and REE in the conventionally dissolved fraction (< 0.22 μm) from upstream to downstream. Arsenic concentration increased from upstream to downstream, especially at the exit of the old mining zone, and was mainly present in the truly dissolved fraction. However, arsenic in the colloid fraction was about 40% upstream and showed a clear decrease when going downstream. Upstream, Fe and Al were mostly present in the colloidal fraction (around 90%, but decreased to 30% downstream for Al). REE patterns suggested that colloidal organic matter played a significant role in metal transport. This was also inferred from the greater enrichment in middle REE as compared to light and heavy REE; this difference in enrichment progressively disappeared with decreasing cut-off filter size. The concentration variations along the length of the river were found to be a combined effect of the changes in lithology and input of contaminants from storage areas or alluvial table.